SURVEI JENTIK NYAMUK ANOPHELES SP SEBAGAI UPAYA PROGRAM ELIMINASI MALARIA - Utama, D.A.; Mustafa, Y.; Faisal, Faisal; Syafruddin, Syafruddin; Hiola, T.T.; Mustafa, R. (Buletin Udayana Mengabdi; Vol 22 No 4 (2023): Buletin Udayana Mengabdi, 2023)
Mosquito control as a vector of malaria transmission is an effort to minimize malaria cases in the community. One of the elimination efforts that can currently be done includes surveillance of malaria through larval examination activities in mosquito breeding places. The purpose of implementing community service is to assist cadres and the community in carrying out epidemiological investigations in the form of larvae surveys in order to support malaria elimination efforts in Telaga Jaya District. The method of implementing this activity is carried out by larvae inspection at a location that is suspected as a place for mosquito breeding. In this activity, the results of the Larvae Container Index (CI) in Bulota Village ranged from 0.4 to 1.2, while in Hutadaa Village they ranged from 0.5 to 1.2. The habitat index in Bulota Village is 80%, with an average distance of discovery of larvae with settlements ranging from 5 to 20 meters. While the Hutadaa Village Habitat Index is 60% with an average distance of the discovery of larvae with settlements ranging from 5 to 10 meters. Among the various types of containers examined, which have the highest chance of breeding Anopheles sp. is a swamp, with An. barbirostris as the most common species of mosquito larvae at the location of the asset. Keywords: surveillance, anopheles, survey of mosquitoes larva, Telaga jaya